Billy Wilder : dancing on the edge - McBride, Joseph, 1947- (New York : Columbia University Press, 2021)
"From Some Like it Hot and The Apartment to Double Indemnity and Sunset Boulevard, Billy Wilder directed some of Hollywood's most iconic movies. However, the roots of Wilder's directorial vision and worldview were very much shaped by his Austrian background and experiences working as a journalist in Berlin at the dawn of Hitler's rise to power. Though a fixture in Hollywood, Wilder always felt an outsider and his perspective as an exiled Jew provided his films with a distinct view of the flaws and possibilities of American and European society. In Billy Wilder and the Phantoms of the Past, Joseph McBride argues, that the director was a stubborn romanticist, whose films mixed critique and compassion. Despite their satirical nature and exposure of hypocrisies of all kinds, Wilder's films were skeptical of cynicism and interested in how people overcome their disillusionment. Mixing biography with analysis of Wilder's films, including some of the later more forgotten works, Joseph McBride explains how Billy Wilder became Billy Wilder"--
Ausländisch -- "A keen observer" -- "Film, that's no profession for adults" -- "I was not in the right country" -- Brackettandwilder . . . and Lubitsch -- Dancing on the edge -- "Not a funnyman but a moralist" -- "I am no longer afraid" -- "Tap-dancing on the grave of Hollywood".
Includes bibliographical references, filmography, and index.
Description based on online resource; title from digital title page (viewed on October 27, 2021).
JSTOR
Keywords: Wilder, Billy, -- 1906-2002.; Wilder, Billy, -- 1906-2002; Motion picture producers and directors -- United States -- Biography; Austrians -- United States -- Biography; Jews -- United States -- Biography; Motion pictures -- United States -- History -- 20th century; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies; Autrichiens -- États-Unis -- Biographies; Juifs -- États-Unis -- Biographies; Cinéma -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS / Film & Video / Direction & Production; Austrians; Jews; Motion picture producers and directors; Motion pictures; United States; 1900-1999; Biographies; History